The MNU Plus Testosterone Rat Model of Prostate Carcinogenesis. (June 2022) - Bosland, Maarten C.; Schlicht, Michael J.; Horton, Lori; McCormick, David L.
Animal models of prostate cancer are essential to identify chemopreventive treatments against this major male malignancy. The N -methyl- N -nitrosourea (MNU) plus testosterone rat model of prostate carcinogenesis is a reliable animal model that recapitulates human prostate cancer in many respects and has been used extensively in chemoprevention studies with good predictive value for the results of human clinical trials. The objective of this article is to describe the induction protocol of this model, demonstrate its robustness and reproducibility over time and across rat strains, provide diagnostic criteria for the identification of prostate lesions, and present the current tumor induction protocol so that others can use this model in a reliable manner. The majority of accessory sex gland tumors in this model are adenocarcinomas originating in the anterior and dorsolateral prostate that metastasize to lungs and abdominal structures. The rat strain used is of critical importance, with the commercially available Wistar WU and Fischer F344 strains yielding the highest tumor incidences. Low dose, long-term testosterone treatment is essential for a high tumor incidence, but in advanced stage, large adenocarcinomas do not appear to be androgen dependent. This rat model is a robust and reproducible prostate cancer animal model of human prostate cancer.